An unusual case of Aβ2M amyloid deposition in bladder cancer in a non‐dialysis patient. Issue 4 (1st February 2019) - Ishii, Aya; Tei, Yasuhide; Murakami, Tomoyuki; Notohara, Kenji
Abstract : β2‐microglobulin‐related (Aβ2M) amyloidosis (dialysis‐associated amyloidosis) is a common complication in long‐term dialysis patients. An increased concentration of β2‐microgloblin (β2‐m) in the serum appears to be a prerequisite for Aβ2M amyloidosis, in turn causing Aβ2M amyloid deposition predominantly in the osteoarticular tissue. There are few reports, however, of Aβ2M amyloid deposition in non‐dialysis patients. We describe an atypical case of a non‐dialysis patient with Aβ2M amyloid deposition in bladder cancer. A Japanese man in his 80s with no history of dialysis was admitted for transurethral resection of bladder cancer. Histopathological analysis revealed a small amount of amyloid deposition in the small‐vessel wall of both the peripheral urothelial carcinoma and necrotic area. Amyloid typing by immunohistochemistry was strongly positive for anti‐β2‐m antibody, and β2‐m was most frequently detected in laser microdissection‐liquid chromatography tandem mass spectrometry. Although Aβ2M amyloidosis was expected, contrary to this, the patient's serum β2‐m was only 4 mg/L, although his urine β2‐m level was increased at 1340 mg/L. The unique findings observed in our patient may contribute to the elucidation of the novel pathogenesis of Aβ2M amyloid fibril formation that is distinct from conventional Aβ2M amyloidosis.